TATA KELOLA PERUSAHAAN DAN KINERJA KEUANGAN TERHADAP VALUE OF THE FIRM PADA PERUSAHAAN PROPERTI DI INDONESIA - Sunita Dasman; Reva Meliyana; Widiastuti Widiastuti (LP2M Universitas Bina Bangsa, 2023)
The purpose of this research is to examine whether corporate governance and financial performance affect the firm value of property companies in Indonesia. Purposive sampling was used in the research sample collection and obtained 11 of 66 property companies for the 2015-2019 period. The data is obtained from the financial reports of property companies listed on the Indonesia Stock Exchange. The data processing technique used is panel data regression analysis. The results of this study indicate that increased leverage and profit have an impact on increasing the value of the firm. Meanwhile, the increase in the number of independent commissioners and managerial ownership has no impact on increasing the value of the firm